1968
DOI: 10.2307/1237625
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Marketing Order on Winter Carrot Prices

Abstract: Marketing orders are utilized for the express purpose of improving returns to growers. Higher quality requirements and supply or rate-of-flow management are the major too]s in sucia an eltort. The adoption of the marketing order for South Texas carrots permitted a limited test of the hypothesis that derived demand would increase du¡ the order period. The hypothesis is reasonable because of the relatively low quality image of Texas winter carrots. It appears that demand at the grower level in Texas did increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Her conclusions depend on the way quality standards are defined. According to Bockstael, if standards are based on product charac- 45 Other relevant work on this subject includes a theoretical study of Price (1967) and an empirical study of Shafer (1968). These studies suffer from the limitation that minimum quality standards have not been explicitly integrated in the supply and demand analysis (Bockstael 1984).…”
Section: Minimum-quality Standardsmentioning
confidence: 99%
“…Her conclusions depend on the way quality standards are defined. According to Bockstael, if standards are based on product charac- 45 Other relevant work on this subject includes a theoretical study of Price (1967) and an empirical study of Shafer (1968). These studies suffer from the limitation that minimum quality standards have not been explicitly integrated in the supply and demand analysis (Bockstael 1984).…”
Section: Minimum-quality Standardsmentioning
confidence: 99%
“…Ninety-one percent of the variation in Texas carrot prices was explained by the quantity, temp, and rainfall variables plus a shift or indicator variable for the 1966 season. The estimated coefficients indicated that the price of Texas 48-1's mesh declined 62 cents if Texas shipments increased by 100 carlots and by $1.42 if California shipments increased by 100 carlots; that each inch of rain in the Lower Rio Grande Valley, Texas in September raised price by 20 cents; that a one-degree rise in the avg high temp in week t-1 lowered price by 4 cents and in week t-2 by 3 cents; and that temporary conditions, perhaps the market order (8), raised prices by 85 cents in the winter of 1966 above the winters of 1967 and 1968. Los Angeles prices of 50-lb.…”
Section: San F R a N C I S C Omentioning
confidence: 99%
“…In the November 1968 issue of this Journal, Professor Carl E. Shafter [1] examined the effect of a marketing order on winter carrot prices. We wish to suggest that there are some logical inconsistencies in his paper that appear to arise out of improper specifi-We are indebted to G. Edward Schuh for encouragement and helpful comcomments.…”
Section: The Effect Of a Marketing Order On Winter Carrot Prices: Commentioning
confidence: 99%
“…1 Mr. Abaelu is unable to comment because of conditions prevailing in the Biafran section of Nigeria. and myself.…”
mentioning
confidence: 97%